The GCC Monetary Union : Some Considerations for the Exchange Rate Regime - Guerami, Behrouz; Abed, George; Erbas, S. (Washington, D.C. : International Monetary Fund, 2003)
We compare the dollar peg to a dollar-euro basket peg as alternative exchange rate regimes for the incipient Gulf Cooperation Council (GCC) currency union. Quantitative evidence suggests basket peg does not dominate dollar peg for improving external stability. However, as GCC exports and external financial assets become more diversified, a more flexible exchange policy may be necessary for competitiveness and stability. Pegging the prospective common GCC currency to a basket, like the dollar-euro basket, may provide a conservative transitional strategy toward a more flexible exchange rate policy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet